Design for Manufacturing and Assembly (DFMA) of Handheld Corded Electrical Drill - Rafai, Noor Hakim; Wan, Arielson (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Design for Manufacture and Assembly (DFMA) is an industry tool that helps to reduce assembling costs by improving the assembly process and minimising the number of parts. The hand-held corded electrical drill was chosen as the case study sample in this work. The key for this research is to come up with a new design efficiency and reduced cost of manufacture by comparing the new model and the original model. To improve the design and lower the cost of the Hand-held corded electrical drill, the Boothroyd Dewhurst DFA manual method and DFMA software is used. The CAD models are generated using the Solidworks software, which is then examined using the Boothroyd Dewhurst DFMA software application. According to the findings of this study, assembly time per product reduce from 523.47 seconds to 482.19 seconds when using the software analysis while using DFA manual method the assembly time per product part is reduce from 532.47 second to 472.19 second. The DFMA result demonstrates that the cost per product is reduced from RM113.78 to RM103.69. As a result, it has been demonstrated that the Boothroyd Dewhurst DFA manual method and DFMA software method approach was capable of improving the design in terms of design efficiency, product assembly time, and cost reduction. This strategy can be used in the manufacturing business to improve design effectiveness and estimate the cost of production for newly design product.